Meningkatkan Keterampilan Khat Imla’ dengan Pengembangan Modul - Handayani, Novita Fitri; Koderi, Koderi; Kesuma, Guntur Cahaya; Erlina, Erlina (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
The background of this research is that when students learn Arabic language skills they have difficulty in writing Arabic. This study aims to develop and analyze the feasibility of khat and imla 'materials for seventh grade students of Madrasah Tsanawiyah. This development research uses the Borg and Gall development research model with six stages. The results of this study indicate that teaching materials have been developed according to the Borg and Gall seven-step model, namely problem and potential identification, information gathering, product design, design validation, design revision, product testing, and product revision. The results of the validation of the developed teaching materials showed that the material experts assessed that the developed product was very well qualified, the learning expert was very well qualified, and the media expert was also very well qualified.